IMPROVING THE LOGISTICAL PROCESSES IN CORPORATE SERVICE SYSTEM - Irina MAKAROVA; Rifat KHABIBULLIN; Eduard BELYAEV; Larisa GABSALIKHOVA; Eduard MUKHAMETDINOV (Transport Problems, 2016)
The study deals with enhancing the reliability of freight cars by improving the corporate service system. Assessing of the quality of spare parts suppliers is discussed. An algorithm for supplier selection and an evaluation method, based on cluster analysis of indicators of supplier reliability, is proposed. Alternative developments for a service network, in view of expanding of the car fleet powered by natural gas-based fuel have been considered.